Performance Study of AODV, GRP and OSPFv3 MANET Routing Protocols Using OPNET Modeler (Journal of Engineering, 2013)
A Mobile Ad hoc Network (MANET) is a collection of mobile nodes, that forms on the fly a temporary wireless multi-hop network in a self-organizing way, without relying on any established infrastructure. In MANET, a pair of nodes exchange messages either over a direct wireless link, or over a sequence of wireless links including one or more intermediate nodes. For this purpose, an efficient routing protocol is required. This paper introduced performance study of three of MANET protocols (AODV, GRP and OSPFv3). This study was one of the newer studies because wireless communication played an important role in today’s application and the field of mobile ad hoc network becomes very popular for the researchers in the last years. This study was done using OPNET Modeler v14.5 and the comparison between the protocols was done in terms of throughput, routing traffic received, traffic sent, load and delay with increased number of mobile nodes from 10, 25 and 50 mobile nodes. The results showed that AODV (reactive routing protocol) was better in delay and had smaller load and smaller throughput than GRP (reactive and proactive routing protocols) and OSPFv3 (proactive routing protocols).